Consequences of knowledge hiding: The differential compensatory effects of guilt and shame. Issue 2 (26th November 2018) - Burmeister, Anne; Fasbender, Ulrike; Gerpott, Fabiola H.
Abstract : The nature of the consequences of knowledge hiding, defined as an intentional attempt to withhold knowledge that has been requested, and the mechanisms through which knowledge hiding affects outcomes are undertheorized. In this research, we propose that knowledge hiding can evoke guilt and shame in the knowledge hiding perpetrator. We zoom into the three types of knowledge hiding – evasive hiding, playing dumb, and rationalized hiding – and predict that the more deceptive knowledge hiding types, namely evasive hiding and playing dumb, evoke stronger feelings of guilt and shame than rationalized hiding. We further argue that guilt and shame trigger differential emotion‐based reparatory mechanisms, such that guilt induces the motivation to correct one's transgressions through organizational citizenship behaviour (OCB), whereas shame induces the tendency to withdraw after hiding knowledge, as reflected in lower levels of OCB. We test the proposed positive indirect relation between knowledge hiding and OCB via guilt, and the proposed negative indirect relation via shame in a scenario‐based experiment and a two‐wave field study. The studies provided support for most of our hypotheses. We discuss how the proposed emotion pathway can facilitate nuanced theorizing about consequences of knowledge hiding for different types of negative emotions and subsequent compensatory work behaviours. Practitioner points: Hiding knowledge from colleagues can lead to experiences of guilt and shame. Playing dumb (in contrast to evasive hiding and rationalized hiding) in particular elicits these negative emotional experiences. Practitioners should therefore aim to prevent knowledge hiding, and especially playing dumb, in organizations. Guilt and shame elicit differential action tendencies in knowledge hiding perpetrators, which entails that negative emotions as a result of playing dumb can sometimes lead to positive behavioural consequences. To effectively manage the consequences of knowledge hiding, practitioners should try to elicit constructive negative emotions (guilt) rather than destructive emotions (shame) as a reaction to employees' knowledge hiding. This can facilitate employees' compensation for their transgressions through organizational citizenship behaviour, rather than withdrawal from the situation.